2021
DOI: 10.1055/s-0041-1730884
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Surrogate Markers of Insulin Resistance with Fasting Insulin in Type 2 Diabetes Mellitus Patients: A Study of Malwa Population in Punjab, India

Abstract: Context Insulin resistance (IR) and abnormal insulin secretion play a key role for the development of type 2 diabetes mellitus (DM). Aims We investigated the surrogate markers of IR, i.e., Homeostasis Model Assessment (HOMA), Quantitative Insulin Sensitivity Check Index (QUICKI), McAuley, and Fasting Insulin Resistance Index (FIRI) in type 2 DM patients. Also, fasting insulin (FI) levels were estimated in type 2 diabetics. Further, the correlation of FI with other surrogate markers of IR in type 2 DM was done.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The HOMA model has proved to be a robust clinical and epidemiological tool for assessing IR (HOMA-IR) and β-cell function (HOMA-β). HOMA-IR correlates well with the HEC tests ( 94 ), with a sensitivity of 86%, specificity of 100%, and accuracy of 88% ( 66 ). No difference was found between benign and malignant cases using the Indonesian cut-off ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The HOMA model has proved to be a robust clinical and epidemiological tool for assessing IR (HOMA-IR) and β-cell function (HOMA-β). HOMA-IR correlates well with the HEC tests ( 94 ), with a sensitivity of 86%, specificity of 100%, and accuracy of 88% ( 66 ). No difference was found between benign and malignant cases using the Indonesian cut-off ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another derived IR marker is FIRI, with a sensitivity of 86%, specificity of 100%, and accuracy of 88% ( 66 ). Among all patients with ovarian neoplasms, the present study revealed that the median score of FIRI was 0.76 (IQR: 0.54-1.35) and was not significantly different between the benign and malignant groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations